Effectiveness of Cadaver Compared to Plastination as Anatomy Learning Media: Medical Student Perspective (Althea Medical Journal, 2025)
Background: Anatomy is a fundamental component of medical education, playing a pivotal role in understanding the structure and function of the human body. Cadaver-based anatomy learning remains widely used in many medical faculties; meanwhile, plastination as an alternative method, offering efficiency and practicality. This study aimed to evaluate the effectiveness of cadaver and plastination learning media in improving anatomical understanding among first-year medical students.Methods: This was a cross-sectional quantitative study with a pretest-posttest control group design conducted in November-December 2023. The study included 69 first-semester medical students from the Universitas Pertahanan, Republic of Indonesia who had not previously received musculoskeletal anatomy lectures. Participants were divided into cadaver and plastination groups. A questionnaire was distributed before and after the anatomy class. Data were analyzed with the Mann-Whitney, Wilcoxon, and paired sample t-test.Results: Both cadaver and plastination groups showed a significant increase in post-test scores (p
Keywords: anatomy education; cadaver; plastination; medical students; learning media